NHC‐Capped Cyclodextrins (ICyDs): Insulated Metal Complexes, Commutable Multicoordination Sphere, and Cavity‐Dependent Catalysis1. Issue 28 (3rd June 2013) - Guitet, Maxime; Zhang, Pinglu; Marcelo, Filipa; Tugny, Coralie; Jiménez‐Barbero, Jesús; Buriez, Olivier; Amatore, Christian; Mouriès‐Mansuy, Virginie; Goddard, Jean‐Philippe; Fensterbank, Louis; Zhang, Yongmin; Roland, Sylvain; et al.
<x xml:space="preserve">Abstract</x> Don't slam the door! Cyclodextrins capped with an N‐heterocyclic carbene (ICyDs) entrapped metal ions within their cavity through a novel set of interactions, including X⋅⋅⋅π, which enabled the cavity to be closed by ligand exchange (see scheme; Bn=benzyl). Although insulated from an electrode, the deeply buried metal ions retained catalytic activity. The cavity influenced the regio‐ and stereochemical outcome of the catalyzed reactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>